Regulated expression of cytochrome P-450scc (cholesterol-side-chain cleavage enzyme) in cultured cell lines detected by antibody against bacterially expressed human protein. - Hu, M C (1991)
The first step in the synthesis of steroids is catalysed by cytochrome P-450ssc (cholesterol-side-chain cleavage enzyme). We have investigated the synthesis of this enzyme in three cultured cell lines at the protein and hormone secretion levels. Hormone levels were measured by an enzyme immunoassay using a monoclonal antibody against progesterone. The protein level was detected using polyclonal antibodies directed against a P-450scc fusion protein overproduced in Escherichia coli. Utilizing a bacteriophage T7 promoter expression system, a large amount of human P-450scc fusion protein was produced and easily purified. P-450scc was synthesized in the mouse adrenal tumour cell line Y1 and human choriocarcinoma cell line JEG-3, but not in monkey kidney cell line COS-1. The production of P-450scc in Y1 and JEG-3 cells was stimulated by 8-bromo cyclic AMP, the effect of which was not observed until 6 h after induction and was more pronounced at 24 h. Y1 and JEG-3 cells exhibited a difference in progesterone secretion after induction.